Analysis on the current situation of nursing undergraduates' innovation ability based on nursing basic experiment course after epidemic situation (疫情后基于《护理学基础实验》课程的护理本科生创新能力的现状分析) - ZHANG Ying (张莹); LI Chunxiang (李春香); YAO Yihao (姚一浩); LI Zhaofan (李兆帆); WEN Shubo (温书博); CHEN Wenbo (陈文博) (Association of Integrative Nursing, 2021)
Objective To investigate the current situation of innovation ability of nursing undergraduates after the epidemic situation and analyze its influencing factors. Methods A total of 164 undergraduate nursing students of 2019 grade were investigated by using the innovation ability questionnaire. Results The aggregate score of nursing students' innovation ability was (119. 68±17. 74), the mark of innovation behavior was (19. 74±5. 07) the highest, the score of innovation consciousness was (9. 07±2. 78) the lowest. The results of multiple regression analysis showed that the position, scientific research experience, willingness to participate in scientific research, active communication and attitude to nursing major were the main factors affecting the innovation ability of nursing major students affected by epidemic (P＜0. 05). Conclusion The innovation ability of undergraduate nursing students of Grade 2019 was generally at the middle level. The development should be stressed on teaching, and the innovation ability of nursing students, improving education methods and formulating innovation ability training programs, should be comprehensively improved. (目的 调查护理学院2019级本科生疫情后创新能力的现状及分析其影响因素。方法 自设创新能力问卷进行调查, 共调查164名2019级护理本科生。结果 本院护理学生创新能力得(119. 68±17. 74)分, 其中创新行为最高为(19. 74±5. 07)分, 创新意识最低为(9. 07±2. 78)分。多元回归分析结果表明受疫情影响护理专业学生的职务、科研经验、参与科研意愿、是否主动交流问题及对护理专业的态度是影响创新能力的主要因素(P＜0. 05)。结论 护理学院2019级护理专业本科学生创新能力总体处于中等水平, 教学中应重视护理专业学生创新能力的培养, 通过改善教学方式、制定创新能力培养方案等措施全面提高其创新能力。)